The First Governor of Mecca: ʿAttāb b. Asīd, His Life and Political Activities - Ümit Eskin (İslami İlimler Dergisi, 2022)
History, while talking about the main actor, the human being,While talking about the leading actor, the human being, history selects and distinguishes people who greatly influence humanity rather than ordinary life stories and depicts these individuals according to the most salient features of their lives and characters. It describes Abel as oppressed, Kabul as cruel, Alexander as a commander, Diogenes as a philosopher, and Ibrāhīm as an admonisher, Nimrod as a dictator. Similarly, it classifies the Companions of the Prophet as the pioneers in their spheres of influence, particularly regarding their virtues. Among them is ʿAttāb b. Asīd. His appointment to the office of governor is a notable development and the mission he undertakes has great importance. He was chosen as the governor of Mecca at a young age when he had just converted to Islam. The appointment of one of the young people of Ḳurays̲h̲ as a leader rather than the prominent Companions while disregarding the question of tribe affiliation is a factor that should be carefully examined. What were the possible causes and consequences of the Prophet having made this appointment? In addition, a study of his life can be used as a basis to answer questions such as whether or not this appointment had a role in forming the basis of the view in Islamic political history that “Imams are from Ḳurays̲h̲.” In this study, the reasons for the election of the first governor of Mecca, its effect on the general public, and its reverberations in Islamic history will be discussed based on the available sources.